DEVELOPMENTAL TRENDS OF SHORT GRAVITATIONAL INSECURITY (SGI) ASSESSMENT AMONG INDIAN CHILDREN - DR.U.GANAPATHYSANKAR; DR.A.PREMA (International Journal of Pharma and Bio Sciences, 2015)
The purpose of this study was to examine the reliability of Short Gravitational Insecurity (SGI) assessment among Indian Children. METHOD:Short Gravitational Insecurity assessment consists of 5 items with two behavioural categories.The Short Gravitational Insecurity Assessment (SGI) was administered to 490 typically developing children in the age group of 3-10 years to determine development trends for SGI assessment for preliminary validation. The SGI assessment was conducted in the standardized format according to the protocol developed for the SGI assessment in a distraction free environment. RESULTS: The results revealed that there was a statistically significant difference in performances between the age groups in Emotional Response (ER), Postural Response (PR) and Total Score (TS) of the SGI assessment. Further, Post hoc analysis revealed that there was a statistically significant difference in one year interval from 3-10 years. CONCLUSION: The present study concluded that SGI has developmental trends. Normative study is recommended to establish a cutoff score for Short Gravitational Insecurity assessment.